An insight into hypothesized biological mechanisms contributing to the Flash effect - Del Debbio, Francesca; Bertilacchi, Maria Sofia; Gonnelli, Alessandra; Da Pozzo, Eleonora; Tozzini, Valentina; Martini, Claudia; Capaccioli, Simone; Costa, Barbara (Frontiers in Physics, 2023)
In recent years, FLASH radiotherapy (FLASH RT) has gained attention in preclinical studies as a potential advancement in cancer treatment. The great advantage of FLASH RT is the ultra-fast, high doses delivery that have a similar or greater effect on cancer cells while sparing normal, healthy tissue surrounding the tumor site. This is known as the FLASH effect. However, currently, there are not enough in vitro and in vivo data to transpose FLASH RT to human trials. This mini review summarizes the available in vitro data on electron beam FLASH, focusing on possible mechanisms of the FLASH effect. Current studies have focused on various types of cancer, including lung cancer, glioblastoma, uterus adenocarcinoma, cervix carcinoma, prostate carcinoma, melanoma, breast cancer, head and neck squamous cell carcinoma, and colon adenocarcinoma. Several hypotheses have been proposed to explain the biological mechanisms contributing to the to the selective FLASH effect, including differences between healthy and cancer cells in production of reactive oxygen species and free radicals, limitation of Fenton reaction caused by high Fe2+/3+ levels in tumor cells, and impaired DNA damage repair mechanisms occurring in cancer.